Qadariyah dan Jabariyah di Era Modern: Refleksi Memahami Kehendak dan Takdir - Ahmad Diaz Makmur; M. Ilham; Barsihan Nor (Fikr: Jurnal Pemikiran Studi Islam, 2025)
This paper aims to examine in depth the fundamental conceptual differences between the Qadariyah and Jabariyah schools of Islamic theology regarding human free will and divine destiny, as well as the relevance and academic contribution of these two views in shaping the ethos and perceptions of society in the modern era. This research is driven by fundamental changes in society's views on the concepts of will and destiny as a result of advances in education and technology. This paper uses a qualitative research method with a content analysis approach to primary and secondary literature, focusing on classical theological texts and contemporary journals, to specifically analyze the arguments and social implications of both schools of thought. The results show that Qadariyah, which emphasizes individual free will and responsibility, promotes the values of empowerment, innovation, accountability, and optimism. Conversely, Jabariyah, which believes that all events are predetermined by Allah's will, teaches the values of acceptance, inner peace, humility, and gratitude. Overall, understanding this theological dichotomy is highly relevant as a framework for addressing ethical, moral, and technological advancement challenges in contemporary society